The role of informal green spaces in reducing inequalities in urban green space availability to children and seniors - Sikorska, Daria; Łaszkiewicz, Edyta; Krauze, Kinga; Sikorski, Piotr (Environmental science & policy, 2020)
•Residents in both Warsaw and Łódź are subject to unequal accessibility to urban green spaces.•The greenery associated with transportation routes, multi-family housing and agriculture have the greatest potential to complement formal UGS.•In Łódź, it is children who are most disadvantaged in terms of access to UGS, while in Warsaw it is elderly citizens.•Disparities among children and elderly citizens in access to formal green spaces can be reduced by informal green spaces.•Preservation of unmanaged areas can allow access to green spaces and enable more contact with nature close to home. Urban green spaces (UGS) offer a wide range of ecosystem services to city dwellers, contributing to their health and well-being. The resources of formally designated UGS, such as parks and forests, are frequently underprovided, however. This results in unequal access to UGS, which has become an environmental justice issue. We investigated the potential of informal green spaces (IGS) to complement existing formal UGS to reduce distributional inequity in UGS availability. We focused on the most vulnerable groups of citizens, children and elderly residents, for whom the availability of UGS plays a particularly important role. The study was performed in two Eastern-European cities, Warsaw and Łódź, both characterised by a well-developed system of UGS but of different spatial composition and UGS configuration. We focus on unmanaged areas within IGS and link them to the provisioning of recreational ecosystem services, such as enabling direct contact with nature. We identified different categories of formal and informal UGS based on publicly available data, supported by NDVI values, followed by UGS availability analysis of formal and informal UGS in the service area of 300 m for each residential building. We found that informal UGS are equally important as formal ones, and they may contribute to better access to selected urban ecosystem services. Both cities are characterised by unequal distribution of formal UGS. In Łódź, children are least favoured in terms of UGS availability, while in Warsaw, elderly citizens are most excluded. In both cities, it is the green areas associated with transportation routes communication routes, multi-family housing and agricultural lands along with grasslands that have the greatest potential to improve the equal availability of UGS to residents. We propose maintaining various types of unmanaged green areas in cities to help limit disparities to UGS access, and it would also increase their importance in the provisioning of recreational ecosystem services.